Chloroplast Functionality at the Interface of Growth, Defense, and Genetic Innovation: A Multi-Omics and Technological Perspective - Chunhua Zhang; Wenting Li; Yahan Wu; Shengli Li; Bao Hua; Haizhou Sun (Plants)
Chloroplasts are important in plant growth, development, and defense mechanisms, making them central to addressing global agricultural challenges. This review explores the multi-faceted contributions of chloroplasts, including photosynthesis, hormone biosynthesis, and stress signaling, which orchestrate the trade-off between growth and defense. Advancements in chloroplast genomics, transcription, translation, and proteomics have deepened our understanding of their regulatory functions and interactions with nuclear-encoded proteins. Case studies have demonstrated the potential of chloroplast-targeted strategies, such as the expression of elongation factor EF-2 for heat tolerance and flavodiiron proteins for drought resilience, to enhance crop productivity and stress adaptation. Future research directions should focus on the need for integrating omics data with nanotechnology and synthetic biology to develop sustainable and resilient agricultural systems. This review uniquely integrates recent advancements in chloroplast genomics, transcriptional regulation, and synthetic biology to present a holistic perspective on optimizing plant growth and stress tolerance. We emphasize the role of chloroplast-driven trade-off in balancing growth and immunity, leveraging omics technologies and emerging biotechnological innovations. This comprehensive approach offers new insights into sustainable agricultural practices, making it a significant contribution to the field.